Embodiment of Economic Democracy Aspects in National Banking Law - Elyana Novira; Yofiza Media (Green Publisher Indonesia, 2024)
This research discusses the embodiment of aspects of economic democracy in Indonesian national banking law. Economic democracy is defined as a system in which the distribution of wealth and economic opportunity is done fairly and equitably. This research evaluates the extent to which the principles of economic democracy, such as fair access to banking services, financial inclusion, and consumer protection, are implemented in national banking regulations and policies. The method used in this research is qualitative analysis with a normative juridical approach, which involves the study of legal documents and related regulations. The results show that although there are some efforts to integrate the principles of economic democracy in national banking law, there are still gaps in its practical implementation. Recommendations are given to strengthen regulations and policies to be more aligned with the objectives of economic democracy, so that economic benefits can be felt by all levels of society.